Dirasatun tatbiqiyyah lil-suwar al-bayaniyyah (al-majaz) fil-amthal al-yorubawiyyah (2013)
Proverb has been regarded as one of the most precious treasures and heritages that preserve competence, eloquence as well as syntactic and semantic comprehension of any language around the globe. Yoruba Language is one of the major languages out of 656 spoken languages in Nigeria. Consequently the paper opens its study with a brief illustration of the origin of Yoruba proverbs, points of its acquisition and method of its oral transmission from one generation to another. A brief historical status of al-Majaz in Arabic rhetoric which gives birth to metaphor, free and mental figure and metonymy follow as second segment. Besides the rhetorical analysis of the selected proverbs that examines both the linguistic and literary studies also reveals stylistic and rhetorical application of some sentences which transmigrate its real semantic rendition. These also prevail on the rhetorical imagery of the transcendental connotation of both languages. The plausibility of acquisition of intrinsic meaning of a language through rhetorical application coupled with the role of Yoruba proverbs as a protecting means of the language and culture is established Lastly, it reveals the socio- linguistic interference and contrastive application of allegories in form and style in the two languages-Arabic and Yoruba.